A study on IPv4 and IPv6 over ATM - Cao, Hong (2008)
This dissertation introduces a modified ATM address resolution protocol to resolve the communication issues between IPv4 and IPv6 hosts over ATM networks. During transition period of IPv4 to IPv6, IPv4 hosts and IPv6 hosts could co-exist at the same time. This protocol provides a solution for communication between IP hosts of different version over ATM networks.